By looking through an book, I found this interesting series

To prove that:

$$\tan(\theta)+\tan \left(\theta+ \frac{\pi}{n} \right) + \tan\left(\theta + \frac{2\pi}{n}\right) + \dots + \tan \left (\theta + \frac{(n-1)\pi}{n} \right) = -n\cot \left(\frac{n\pi}{2} + n\theta \right)$$

I have tried the Gaussian pairing trick and using:

$$\tan A + \tan B = \tan(A+B) (1-\tan A \tan B)$$


$$\tan A \tan B = \frac{\cos(A-B) - \cos(A+B)}{\cos(A-B)+\cos(A+B)}$$

However I could not do anything of great use.

I also considered perhaps roots of unity of:

$$z^{2n} = \cos \theta + i\sin \theta$$

But that grew to no real use, but it may be an idea for others.

I know I can sum an arithmetic series of the arguments for the cosine and sine functions but I cannot find a source on the internet about the tangent function.

Thank You.

| cite | improve this question | | | | |

$$\tan rx=\frac{\binom r1\tan x-\binom r3\tan^3x+\cdots}{1-\binom r2\tan^2x+\cdots}\text{ (Proof below) }$$

Now, if $\tan rx=\tan r\theta\implies rx=n\pi+r\theta$ where $n$ is any integer

$\implies x=n\frac{\pi}r+\theta$

If $r$ is even, $=2m$(say) $$\tan2m\theta=\tan2mx=\frac{\binom {2m}1\tan x-\binom {2m}3\tan^3x+\cdots+\binom {2m}{2m-1}(-1)^{m-1}\tan^{2m-1}x}{1-\binom {2m}2\tan^2x+\cdots+(-1)^m\tan^{2m}x}$$

$$\implies (\tan2m\theta)\tan^{2m}x+(2m)\tan^{2m-1}x+\cdots=0$$

This is a $2m$ degree equation in $\tan x$

So, $\sum_{0\le n<2m}\tan\left(n\frac{\pi}r+\theta\right)=-\frac{2m}{\tan 2m\theta}=-2m\cot(2m\theta)$

For $n=2m,-n\cot \left(\frac{n\pi}{2} + n\theta \right)=-2m\cot(m\pi+2m\theta)=-2m\cot(2m\theta)$

Similarly for $n$ is odd


Using De Moivre's formula,

$$\sin rx=\binom r1\cos^{r-1}x\sin x-\binom r3\cos^{r-3}x\sin^3x+\binom r5\cos^{r-5}x\sin^5x-\cdots$$ $$=\cos^nx\left(\binom r1 \tan x-\binom r3\tan^3x+\binom r5\tan^5x-\cdots\right)$$ and

$$\cos rx=\cos^rx-\binom r2\cos^{r-2}x\sin^2x+\binom r4\cos^{r-4}x\sin^4x-\cdots$$ $$=\cos^nx\left(1-\binom r2\tan^2x+\binom r4\tan^4x-\cdots\right)$$

On division,

$$\tan rx=\frac{\binom r1\tan x-\binom r3\tan^3x+\binom r5\tan^5x-\cdots}{1-\binom r2\tan^2x+\binom r4\tan^4x-\cdots}$$

| cite | improve this answer | | | | |
  • $\begingroup$ Beautiful solution. Thank You very much. $\endgroup$ – Sy123 Mar 30 '13 at 12:11
  • $\begingroup$ @Sy123, my pleasure. Hope I could make the idea clear. $\endgroup$ – lab bhattacharjee Mar 30 '13 at 15:10
  • $\begingroup$ @labbhattacharjee can you please explain how you reached from If $r$ is even, $=2m$(say) $$\tan2m\theta=\tan2mx=\frac{\binom {2m}1\tan x-\binom {2m}3\tan^3x+\cdots+\binom {2m}{2m-1}(-1)^{m-1}\tan^{2m-1}x}{1-\binom {2m}2\tan^2x+\cdots+(-1)^m\tan^{2m}x}$$ to $$\implies (\tan2m\theta)\tan^{2m}x+(2m)\tan^{2m-1}x+\cdots=0$$.I am afraid i couldnot get it.Thanks. $\endgroup$ – Navin Feb 13 '17 at 12:03
  • 1
    $\begingroup$ @navinstudent, Just cross multiply $\endgroup$ – lab bhattacharjee Feb 13 '17 at 12:04
  • $\begingroup$ @labbhattacharjee just one thing for clarification?are we cross multiplying with $\tan 2m\theta$ or with $\tan 2mx$ $\endgroup$ – Navin Feb 13 '17 at 12:08

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.